2022
DOI: 10.1021/acsomega.1c05932
|View full text |Cite
|
Sign up to set email alerts
|

Phonon Thermal Transport in Silicene/Graphene Heterobilayer Nanostructures: Effect of Interlayer Interactions

Abstract: Heterostructuring, as a promising route to optimize the physical properties of 2D materials, has attracted great attention from the academic community. In this paper, we investigated the room-temperature in-plane and cross-plane phonon thermal transport in silicene/graphene van der Waals (vdW) heterostructures using molecular dynamics simulations. Our simulation results demonstrated that heat current along the graphene layer is remarkably larger than that along the silicene layer, which suggests that graphene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The mechanism of decreasing ITR is associated with the stronger interaction at the interface. [ 43 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of decreasing ITR is associated with the stronger interaction at the interface. [ 43 ]…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of decreasing ITR is associated with the stronger interaction at the interface. [43] Our previous studies have shown that temperature is a key factor affecting the heat dissipation efficiency of microchannels, therefore the trend of ITR with temperature at a defect concentration of 3% are investigated. As shown in Figure 6, the ITRs between graphene and water show a nonmonotonic decreasing trend as the temperature increases.…”
Section: Resultsmentioning
confidence: 99%
“…Carbon-based materials have garnered significant attention due to their versatile and promising applications, in particular, extensive research has focused on the exploration of two-dimensional (2D) carbon materials [ 1 , 2 , 3 ]. The excellent mechanical properties have been widely studied in many aspects, for example, the tensile strength on monolayer and bilayer graphene, the defect influence, the magic angle graphene and the phase transition induced by strain [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. On the other hand, the fullerene system is one of the prominent candidates for future electronic applications as recently proposed in [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous theoretical study also found that enhanced interlayer coupling is conducive to reducing the interlayer ITR of a Gr/silicene vdW heterostructure. [15] Therefore, research of tunable phonon thermal transport in Gr/hBN heterostructures is a key scientific issue for Gr/hBN heterostructure applications. [5] Although the above-mentioned studies have advanced our understanding of thermal transport in Gr/hBN vdW heterostructures, ITR in heterostructures containing both strong covalent bonds and weak vdW interactions has yet to be further explored.…”
mentioning
confidence: 99%
“…We reported our previous work that ITR decreases with increase in the interface coupling strength in vdW heterostructures. [15] Compared with vdW bonding, the covalent bonding in Gr-based thermal interface materials can significantly reduce the thermal contact resistance. This indicates that stronger interatomic interactions are more effective for phonon transport across the interfaces.…”
mentioning
confidence: 99%